Costs of Taxation and the Benefits of Public Goods : The Role of Income Effects - Martin, Will (World Bank, Washington, DC, 2012)
The fact that raising taxes can increase taxed labor supply through income effects is frequently used to justify much lower measures of the marginal welfare cost of taxes and greater public good provision than indicated by traditional, compensated analyses. The authors confirm that this difference remains substantial with newer elasticity estimates, but show that either compensated or uncompensated measures of the marginal cost of funds can be used to evaluate the costs of taxation-and will provide the same result-as long as the income effects of both taxes and public good provision are incorporated in a consistent manner.